Defining the clinicoradiologic syndrome of SARS-CoV-2 acute necrotizing encephalopathy - Lee, Vanessa W.; Kam, Kai Qian; Mohamed, Ahmad R.; Musa, Husna; Anandakrishnan, Poorani; Shen, Qingtang; Palazzo, Alexander F.; Dale, Russell C.; Lim, Ming; Thomas, Terrence (Lippincott Williams & Wilkins, 2024)
BACKGROUND AND OBJECTIVES: We characterize clinical and neuroimaging features of SARS-CoV-2-related acute necrotizing encephalopathy (ANE). METHODS: Systematic review of English language publications in PubMed and reference lists between January 1, 2020, and June 30, 2023, in accordance with PRISMA guidelines. Patients with SARS-CoV-2 infection who fulfilled diagnostic criteria for sporadic and genetic ANE were included. RESULTS: From 899 articles, 20 cases (17 single case reports and 3 additional cases) were curated for review (50 female; 8 were children). Associated COVID-19 illnesses were febrile upper respiratory tract infections in children while adults had pneumonia (45.6) and myocarditis (8.2). Children had early neurologic deterioration (median day 2 in children vs day 4 in adults), seizures (5 (62.5) children vs 3 of 9 (33.3) adults), and motor abnormalities (6 of 7 (85.7) children vs 3 of 7 (42.9) adults). Eight of 12 (66.7) adults and 4 (50.0) children had high-risk ANE scores. Five (62.5) children and 12 (66.7) adults had brain lesions bilaterally and symmetrically in the putamina, external capsules, insula cortex, or medial temporal lobes, in addition to typical thalamic lesions of ANE. Hypotension was only seen in adults (30). Hematologic derangements were common: lymphopenia (66.7), coagulopathy (60.0), or elevated D-dimers (100), C-reactive protein (91.7), and ferritin (62.5). A pathogenic heterozygous c/.1754 C>T variant in RANBP2 was present in 2 children: one known to have this before SARS-CoV-2 infection, and a patient tested because the SARS-CoV-2 infection was the second encephalopathic illness. Three other children with no prior encephalopathy or family history of encephalopathy were negative for this variant. Fifteen (75) received immunotherapy (with IV methylprednisolone, immunoglobulins, tocilizumab, or plasma exchange): 6 (40.0) with monotherapy and 9 (60.0) had combination therapy. Deaths were in 8 of 17 with data (47.1): a 2-month-old male infant and 7 adults (87.5) of median age 56 years (33-70 years), 4 of whom did not receive immunotherapy. DISCUSSION: Children and adults with SARS-CoV-2 ANE have similar clinical features and neuroimaging characteristics. Mortality is high, predominantly in patients not receiving immunotherapy and at the extremes of age.